IPTEK Bagi Masyarakat (IbM) Pembuatan Produk Kewirausahaan Ecospray Hand Sanitizer Berbahan Dasar Eco-Enzym Di Desa Jatikalang Kecamatan Krian Kabupaten Sidoarjo - Rhenny Ratnawati; Pungut; Sri Widyastuti; Sugito (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
Residents of Jatilang Village, Krian District, Sidoarjo Regency have waste problems so they do not understand the use of organic waste and do not have the awareness to process this waste into goods that are beneficial to the economy. The purpose of carrying out this community service activity is to increase the knowledge of the Jatikalang Village community to reduce the household organic waste generated and to make Jatilang Village a village that has the superior product Ecotizer (handsanitizer made from ecoenzym) which can support the economy and family income. Implementation this program consists of several stages, namely site survey, preparation of facilities and infrastructure, procurement of tools and materials, counseling on knowledge about eco enzymes, how to make eco enzymes, and making ECOSPRAY. The result of this activity is that the community has an understanding of processing waste and turning it into useful products with a percentage value of up to 90% of the initial conditions. Through this activity the residents of Jatilang Village are able to properly apply waste management and use it to become a product.